Caribbean Paleodemography : Population, Culture History, and Sociopolitical Processes in Ancient Puerto Rico - Curet, L. Antonio, 1960- (Book collections on Project MUSE., 2005)
According to the European chronicles, at the time of contact, the Greater Antilles were inhabited by the Tainos or Arawak Indians, who were organized in hierarchical societies. Since its inception Carribean archaeology has used population as an important variable in explaining many social, political, and economic processes such as migration, changes in subsistence systems, and the development of institutionalized social stratification. In Caribbean Paleodemography, L. Antonio Curet argues that population has been used casually by Caribbean archaeologists and proposes more rigorous and promisin.